Analysis of Consumer Behavior in Using E-Wallet with Structural Equation Model Method - Yuniarti, Desi; Sari, Nariza Wanti Wulan; Mutmainnah, Dalfa Diandra; Palilu, Dryan Putra; Budi, Ennesya Estya; Hambali, Nidaa Rifdah Rahima (Asian Journal of Science, Technology, Engineering, and Art, 2024)
Current technological advances have changed people's needs for fast, practical, and secure payment systems. Indonesia has now entered the era of the digital economy, where economic activities increasingly rely on digital information and communication technology. In this digital economy, the use of electronic money is on the rise, and Indonesians are starting to adopt payment systems that utilize it. When choosing a digital service, individuals consider factors such as perceived benefits, ease of use, and trust. The purpose of this study is to analyze consumer behavior in using e-wallets through the Structural Equation Model method. This study uses sample data from 55 e-wallet users who are students at Mulawarman University. The results of the analysis show that perceived benefits have a significant influence on consumer behavior; however, ease of use and trust do not significantly affect consumer behavior.